1967
DOI: 10.1002/jez.1401660302
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral studies of inhibition and integration in the mosquito Culiseta inornata (Williston)

Abstract: A study was made of the interaction in the central nervous system of sensory input arising from the simultaneous application of opposing stimuli to receptors on the tarsi and labella of the mosquito. Stimulating chemosensory hairs on the tarsi with 5 M NaCl failed to inhibit the labellar response to sucrose at concentrations above 0.125 M. At lower sucrose concentrations there was a decrease in the number of mosquitoes responding. The application of 5 M NaCl to the tarsal receptors elevated the labellar thresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Results from behavioral studies have indicated that mosquito labellar hairs are sensitive to water, sugar solutions and unacceptable compounds [1][2][3][4][15][16][17][18]. Electrophysiological studies have also shown that these hairs are stimulated by water, sugar, and NaCl [5,15,19].…”
Section: Medium-sized Hairsmentioning
confidence: 99%
“…Results from behavioral studies have indicated that mosquito labellar hairs are sensitive to water, sugar solutions and unacceptable compounds [1][2][3][4][15][16][17][18]. Electrophysiological studies have also shown that these hairs are stimulated by water, sugar, and NaCl [5,15,19].…”
Section: Medium-sized Hairsmentioning
confidence: 99%
“…By contrast, bitter compounds and high concentrations of salts elicit aversive responses. Ammonium chloride or high concentrations of salts evoke rejection responses, such as proboscis withdrawal, and inhibit feeding behavior (23,(43)(44)(45)(46). These responses may have evolved in part to prevent ingestion of harmful food sources.…”
Section: Roles Of the Taste Systemmentioning
confidence: 99%
“…The feeding cues in these simple diets are selected based on the composition of the known mosquito food sources, nectar and honeydew: the three most abundant and one of the less abundant sugars; all 20 naturally‐occurring amino acids; the salt, sodium chloride; and two plant secondary metabolites, caffeine and quinine, previously demonstrated to be detected and discriminated by a variety of insects (Siddiqi & Rodrigues, 1980; Meunier et al , 2003; Hiroi et al , 2004; Thorne et al , 2005; Moon et al , 2006). The two‐choice assay employed in the present study may be more representative of a natural environment than the previously relied upon no‐choice and labellar response assays (Owen, 2005) because it provides the mosquito with the opportunity to feed in an environment that presents a hierarchy of choice: to assess the quality of the two meals on offer and to make a choice. The aim is to produce a basic characterization of mosquito diet acceptance behaviour using a panel of ecologically relevant feeding cues and thus provide the basis for future work assessing mosquito taste‐related behaviours in the context of their natural and more complex diets.…”
Section: Introductionmentioning
confidence: 99%